The enchanted hacienda [large type] - Cervantes, J. C. (Jennifer C.) (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"When Harlow Estrada is abruptly fired from her dream job and her boyfriend proves to be a jerk, her world turns upside down. She flees New York City to the one place she can always call home--the enchanted Hacienda Estrada. The Estrada family farm in Mexico houses an abundance of charmed flowers cultivated by Harlow's mother, sisters, aunt, and cousins. By harnessing the magic in these flowers, they can heal hearts, erase memories, interpret dreams--but not Harlow. Maybe it's not magic she's missing, but belief in herself. When she finally embraces her unique gifts and opens her heart to a handsome stranger, she discovers she's far more powerful than she imagined"--